Effects of low pH and raised temperature on egg production, hatching and metabolic rates of a Mediterranean copepod species (Acartia clausi) under oligotrophic conditions - ZERVOUDAKI, S.; FRANGOULIS, C.; GIANNOUDI, L.; KRASAKOPOULOU, E. (Mediterranean Marine Science, 2013)
This study includes the first information on the combined effect of low pH and raised temperature on egg production rate (EP), hatching success (HS), excretion and respiration of the Mediterranean copepod Acartia clausi. Adult individuals of A. clausi and fresh surface seawater were collected at a coastal station in Saronikos Gulf during April 2012. Four different conditions were applied: two different pH levels (present: 8.09 and future: 7.83) at two temperature values (present: 16°C and present+4 °C= 20°C). EP and HS success decreased significantly over the duration of exposure at future pH at both temperature conditions. However, the analysis of the combined effect of pH, T, chlorophyll α and the duration of the experiments on EP and HS revealed that ocean acidification had no discernible effect, whereas warming; food and the duration of exposure were more significant for the reproductive output of A. clausi. Temperature appeared to have a positive effect on respiration and excretion. Acidification had no clear effect on respiration, but a negative effect on the A. clausi excretion was observed. Acidification and warming resulted in the increase of the excretion rate and the increase was higher than that observed by warming only. Our findings showed that a direct effect of ocean acidification on copepod’s vital rates was not obvious, except maybe in the case of excretion. Therefore, the combination of acidification with the ambient oligotrophic conditions and the warming could result in species being less able to allocate resources for coping with multiple stressors.